The Development of Multicultural Spirit Through The Study of "Tanpa Kata" Novel By Endry Boeriswati - Hariyana, Agustinus; Boeriswati, Endry; Iskandar, Ifan (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2023)
The purpose of this study was to find and develop the multicultural spirit contained in the  Tanpa Kata  novel behind stories about commitment in relationships. The method used was descriptive qualitative and quantitative to obtain preliminary data about the urgency of the spirit of multiculturalism.The population to determine the needs of this research is  as many as 38 students from a total of 73 students in Literary Criticism Course. The sample used was purposive sampling in the form of a novel entitled Tanpa Kata (Without Words). In  addition to being the researchers themselves the instruments used were questionnaires to find out the multicultural attitudes of students in Literary Criticism Courses at the English Language and Culture Department of Darma Persada University.The results of the analysis showed that in the novel studied, though the novel generally told stories about love, but there were found the spirit of multiculturalism.Keywords:  Literature Literacy,  Multiculturalism spirit, Novel Tanpa Kata, Purposive Sampling